Identification and diversity of fibrinogen-related protein (FREP) gene family in Haliotis discus hannai, H. rufescens, and H. laevigata and their responses to Vibrio parahemolyticus infection. Issue 119 (December 2021) - Zou, Yuelian; Xu, Xin; Hu, Qilin; Wang, Yilei; Yang, Huiping; Zhang, Ziping
Abstract: Fibrinogen-related proteins (FREPs) are distributed universally in vertebrates and invertebrates. These proteins contain fibrinogen-like (FBG) domains in their C-terminal region and involve in immune responses and other aspects of physiology in invertebrates. In this study, 54 proteins that contain FBG domains or a fibrinogen_c domain were identified in Haliotis discus hannai . Comparatively, 88 and 63 FREPs were identified from the genomes of H. rufescens and H. laevigata . Most FREPs of abalones had a conserved motif containing a bound calcium ion site and a second conserved motif containing a polymerization pocket site. By sequence analysis, 394 SNPs and 11 Indels were identified in 20 FREP genes of the whole genome of H. discus hannai ; 992 SNPs and 42 Indels were found in 64 FREPs of H. rufescens, and 192 SNPs and 12 Indels were found in 21 FREPs of H. laevigata . Among these SNPs, 92 missense mutation sites were identified in 26 FREP genes of H. rufescens, and 12 were identified in 8 FREP genes of H. laevigata . Due to the poor genomic integrity, annotations of the SNPs or Indels in H. discus hannai did not yield missense mutant sites. FREP genes with polymorphisms were ubiquitously expressed in all the tested tissues; however, the expression is lowest in the hemolymph. In response to Vibrio parahemolyticus infection, expression of FREP genes was significantly upregulated at different exposure times in gills, hepatopancreas, and hemolymph in H. discus hannai . Overall, this study documented the FREP genes of abalones and shed light on the role of FREPs in the innate immune system of these aquaculture species for the prevention and control of diseases. Highlights: 54 proteins that contain FBG domains or a fibrinogen c domain were identified in Haliotis discus hannai . 88 and 63 FREPs were identified from the genomes of H. rufescens and H. laevigata, separately. 394 SNPs and 11 Indels were identified in 20 FREP genes of the whole genome of H. discus hannai . 992 SNPs and 42 Indels were found in 64 FREPs of H. rufescens, and 192 SNPs and 12 Indels in 21 FREPs of H. laevigata . Vibrio exposure upregulates expression of FREP in gills, hepatopancreas, and hemolymph of H. discus hannai .